Sobre el concepto de intertextualidad: teoría y práctica - Wahnón, Sultana (Estudios bíblicos, 2022)
This work is a theoretical introduction to the concept of intertextuality. After informing about the authorship of the term, the article describes the role that Bakbtinian-Kristevian ideas played in the crisis of the first structuralism and, consequently, in the gestation of French post-structuralism. The revision that is made here on the contributions of Kristeva, Barthes and Genette proves that the theory of intertextuality was born in opposition and conflict with the immanentism typical of structuralist works, but without this entailing the recovery of the extrinsic approaches that this school he bad set out to fight. The work closes with a section that highlights the relevance of Genette’s contribution and offers some examples of how his concepts could be used in the field of Biblical studies.